Associative long-term potentiation in hippocampal slices. - Barrionuevo, G (1983)
Interactions between two excitatory monosynaptic inputs to hippocampal neurons of the CA1 region were examined in the in vitro slice. By adjusting the strengths of the electrical stimuli delivered to the two input pathways, one was made to generate a weak and the other a strong synaptic response. Simultaneous tetanic stimulation of both input pathways resulted in a subsequent long-term enhanced synaptic efficacy in the weak input under conditions in which the same tetanic stimulation of either input alone failed to have this effect. This form of long-term synaptic potentiation (LTP), known as associative LTP, was shown in some cases to last hours without decrement. The plastic changes were localized within the CA1 region and appear to reside in the pre- or postsynaptic elements of the monosynaptic excitatory input to the pyramidal neurons. The increased synaptic efficacy could not be accounted for by any of several measured postsynaptic passive membrane properties.